Harmful Consequences of Problem Gambling - Denčić, Maja (Zbornik Instituta za kriminološka i sociološka istraživanja, 2023)
In the modern world, gambling is a highly profitable entertainment industry in which a growing number of people participate. Although most people practice gambling as a form of entertainment or recreation in their free time, for a certain part of the population, gambling goes beyond entertainment and turns into a problem gambling behavior with many harmful consequences. In the last four decades, at the international level, significant theoretical and empirical material has been accumulated on problematic gambling and its harmful effects and consequences. On the other side, empirical experiences on this topic are almost absent in Serbia, although we are witnessing the number of available gambling venues growing rapidly nationally. The goal of this paper is to, based on scientific knowledge from around the world, draw the attention of the public in Serbia to the importance and need for more extensive scientific research on problematic gambling and its harmful consequences in this space. The paper analyzes available empirical material published in the period between 1984 and 2022 in Australia, North America, Asia, and Europe.